From ZnSn(OH)6 to SnS2: Topotactic transformation synthesis of SnS2 hierarchical microcubes with superior Li-ion storage performance. (December 2017) - Ji, Shaomin; Yu, Litao; Xu, Xijun; Zhang, Liguo; Liu, Jun
Graphical abstract: Highlights: Uniform 3D hierarchical SnS2 microcubes were synthesized via a topotactic transformation route. The anode of these 3D SnS2 microcubes exhibited stable cycling performance. The anode of these 3D SnS2 microcubes also showed superior rate capability. Abstract: The 3D hierarchical microstructured electrodes by assembling the individual 1D/2D nanosubunits can fully take advantage of the merit of 1D/2D nanostructured materials, as well as alleviate their drawbacks. In this work, SnS2 3D hierarchical microcubes consisting of 2D nanosheet subunits were facilely synthesized via a simple topotactic transformation with room-temperature coprecipitated ZnSn(OH)6 microcubes as the template. Compared to bulk counterparts, this microstructured SnS2 was found to have a unique morphology and electrochemical interfacial regions that facilitated highly efficient Li-ion insertion/extraction and effectively accommodate the large volume changes during charge/discharge cycles. Over the whole 200 cycles at 1C current density, an outstanding cycleing stability is exhibited, with a high stable specific capacity of about 640 mA h g −1 .